Optimal Localization of the Foramen Ovale for Transseptal Puncture Using the Vertebral Body Units - Dong Hoon Kang; Sung Eun Park; Jong Woo Kim; Seong Ho Moon; Ho Jeong Cha; Jong Hwa Ahn; Joung Hun Byun (Medicina)
Background and Objectives: Although transesophageal or intracardiac echocardiography and radiofrequency needles are employed to guide transseptal puncture, their routine utilization is associated with substantial expense. No reports have analyzed the use of the foramen ovale position to effectively guide transseptal punctures on chest X-rays or computed tomography scout views, which are more cost-effective approaches to safely and effectively guide the procedure. We aimed to find the foramen ovale position on chest computed tomography scout views to effectively guide percutaneous transseptal punctures. Materials and Methods: The study population included 31 patients treated with extracorporeal membrane oxygenation (ECMO) for cardiogenic shock, 32 patients diagnosed with atrial fibrillation (AF) who underwent MDCT, and 197 patients who underwent MDCT for non-cardiac conditions. Vertebral body units, defined as the distance between two adjacent vertebral bodies (the sixth and seventh thoracic spines) inclusive of the intervertebral disk space, were used to express the distance from the carina to the foramen ovale on computed tomography scout views. Results: The mean vertebral body units, distance from the carina to the foramen ovale (carina–foramen ovale), and distance from the carina to the foramen ovale on chest computed tomography scout views (carina–foramen ovale vertebral body units−1) were 2.3 ± 0.2 cm, 6.9 ± 0.9 cm, and 3.0 ± 0.3, respectively. Multivariate analysis showed significant correlations between the carina–foramen ovale vertebral body units−1 and sex (β = 0.080; p = 0.028), body mass index (β = −0.020; p < 0.001), age (β = 0; p = 0.013), and the application of extracorporeal membrane oxygenation or the presence of atrial fibrillation (β = 0.130; p = 0.004). Conclusions: Although a three-dimensional approach was not employed, the foramen ovale position may serve as a radiologic guide in various clinical settings where transseptal punctures are required. This technique may be an effective aid in transseptal puncture procedures.